An investigation into the lung function, health-related quality-of-life and functional capacity of a cured pulmonary tuberculosis population in the Breede Valley, South Africa : a pilot study - Daniels, Kurt John (Stellenbosch : Stellenbosch University, 2015)
Thesis (MScPhysio)--Stellenbosch University, 2015.